DINAMIKA TRANSFORMASI MEDIA - Galihpriambodo; Karin Nurliza Azzahra (Jurnal Ilmu Komunikasi Balayudha, 2024)
ABSTRACTMedia transformation has become one of the most striking trends in recent decades. This transformation has led to significant changes in the way media operates, is distributed, and consumed. One of the most important changes that have occurred is the shift from traditional media to digital media. Traditional media, such as television, radio, and newspapers, have been replaced by digital media, such as the internet, social media, and mobile devices. This change has led to increased accessibility to information and communication, as well as reduced production and distribution costs. Another change that has occurred is the transformation in media business models. Traditional media, which relied on advertising revenue, has faced significant challenges from digital media, which depends on subscription and digital advertising revenue. This change has led to media ownership consolidation, with large media companies increasingly dominating the media industry. Media transformation has also impacted politics. Media has become an increasingly important force in the political process, often acting as an opposition agent to the government. Media transformation has also changed the way political campaigns are conducted, with political campaigns increasingly relying on digital media to reach voters.Kata kunci: media economy, media politics, media transformation